The effect of visual biofeedback on balance in elderly population: a systematic review - Alhasan H (Dove Medical Press, 2017)
Hammad Alhasan,1 Victoria Hood,2 Frederick Mainwaring2 1Physiotherapy Department, Faculty of Applied Medical Science, Umm al-Qura University, Mecca, Kingdom of Saudi Arabia; 2School of Health Science, University of Nottingham, Nottingham, Nottinghamshire, UK Background: Balance is commonly affected by multiple factors, especially among the elderly population. Visual biofeedback (VBF) is an intervention tool that can be used in balance rehabilitation.Aim: This study aimed to systematically review randomized controlled trials that examine whether VBF training is effective in improving balance in an elderly population.Data sources: Three databases were searched: CIAHL, EMBASE, and MEDLINE. The searches were limited to the period from 2010 to 2016.Eligibility criteria: Healthy adults, aged ≥65 years, with no specific disorders were included. Interventions were any VBF intervention with the aim of improving balance and were compared to no intervention, traditional exercises, placebo, or standard care. The outcome measures were balance as measured by any validated outcome measure.Studies appraisal method: The Physiotherapy Evidence Database quality assessment tool and The Cochrane Collaboration tool for assessing risk of bias were used by two independent authors (HA and FM) in order to appraise the included studies.Results: The database search resulted in 879 articles, of which five papers were included. VBF was compared to no intervention, a placebo, and traditional exercise. The total number of participants in all the five included studies was 181, with a mean age of 74.3 years (standard deviation 6.7). Two studies were rated as high-quality studies, and three were rated as fair quality.Conclusion: Engaging elderly people living in the community in VBF training was found to be effective and could improve their balance ability. However, the variation between studies in methodology, intervention protocol, and outcomes utilized made it difficult to inform a definitive statement regarding the potential application of VBF for balance training with the elderly. Furthermore, high-quality randomized control trials are required. The systematic review level of evidence is moderate, and the strength of recommendation is that VBF is likely to be beneficial. Keywords: visual feedback, exergames, older adult, postural balance